Thermographical Measuring of the Skin Temperature Using Laser Needle Acupuncture in Preterm Neonates. (14th May 2012) - Raith, Wolfgang; Litscher, Gerhard; Sapetschnig, Iris; Bauchinger, Sebastian; Ziehenberger, Evelyne; Müller, Wilhelm; Urlesberger, Berndt
Abstract : In children, laser acupuncture is used more often than needle acupuncture in Western countries, due to their aversion to needles. When applying laser acupuncture to premature babies and neonates, firstly the degree of the thermal increase to the skin has to be evaluated so as to guarantee safe application. The patients were premature neonates before their discharge from hospital. The measurements were carried out by means of a polygraphy while they were asleep shortly. The large intestine 4 acupoint (LI4, Hegu ) was stimulated by a microlaser needle (10 mW, 685 nm) twice (5 and 10 min). Local thermographic pictures were taken with a thermal camera (Flir i5, Flir Systems Inc., Portland, USA), and the warmest point was determined and subsequently compared. The study included 10 premature neonates (7 male, 3 female). The measurements were carried out on the 33rd day of life (weight 2030 g, gestational age 36 + 3 weeks of pregnancy). In comparison to the initial temperature (32.9 C ° ), after 5 minutes of stimulation (33.9 ° C) (P = 0.025 ) and also after 10 minutes of stimulation (34.0 ° C) (P = 0.01 ), there was found to be a significant increase in the skin temperature. The singular maximum value of 37.9 ° C bears a potential danger; however, compared to the local temperatures reached in transcutaneous blood gas measurements it appears not to entail any risks.